Flora of Espírito Santo: Humiriaceae - Nepomuceno,Álvaro (2022)
Abstract Belonging to Malpighiales, Humiriaceae has about 65 species in eight genera, distributed almost exclusively in the Neotropics, occurring from southern Brazil to Central America. In Brazil, 35 species have been recorded (ca. 54% of the family’s diversity), wherein the greatest diversity is found in the Amazon (27 spp.), Atlantic Forest (9 spp.) and Cerrado (6 spp.) domains. This work is part of the “Flora do Espírito Santo” project, which aims to contribute to the knowledge of the state’s floristic diversity. Field expeditions were carried out from January/2019 to March/2020. Humiriaceae, in the state of Espírito Santo, is represented by six species distributed in four genera: Humiria, Humiriastrum, Sacoglottis and Vantanea. Among the registered genera, Vantanea is the most diversified, with three species. In the dense rain forest, all Humiriaceae species recorded here were found, followed by pioneer formations of restingas, with four species and seasonal semideciduous forest, with one species. The main morphological characters that assist in the delimitation of Humiriaceae species in Espírito Santo, are androecium characteristics, such as length (homodynamous or heterodynamous), number of stamens and the number of their series, as well as anther morphology.